Kajian Monokultur dan Tumpangsari Tanaman Teh dengan Cabai di Beberapa Kemiringan Lereng terhadap Perubahan pH Tanah dan Ca-dd - Restu Wulansari; Eko Pranoto (Jurnal Penelitian Teh dan Kina, 2018)
The utilization of tea area especially on young tea period to intercropping was one of the efforts to keep the income stability, especially on tea smallholder plantation scale. Chilli was one of the plants planted on the tea area by the intercropping system. But, chili has different habitat and characteristics than tea, especially on soil pH characteristics. The optimum pH to the growth of Chili on 6–7, otherwise tea on 4,5–5,6. Generally, chili needs dolomite around 3,66–6,83 tones per hectare if the difference of pH around 1,0–2,0. The research aimed to evaluate the soil pH and exchangeable-Ca (Ca-dd) on Monoculture and Intercropping tea with chili on the selected slope of the area. The experiment was conducted at the Experimental Garden of Research Institute for Tea and Cinchona, West Java, on the young tea area age two years. The Split Split Plot experimental design was used with three repetitions. As Main Plot was Planting System (Intercropping and Monoculture System); while the sample position (between plant and row of the plant) was as Sub Plot and Sub Sub Plot was Land Slope (8-15%, 16-25%, dan >25%). The result shows that the intercropping system tea with chili caused the Ca-dd and soil pH higher compared to that monoculture system. But, the land slope was not significantly influencing the Ca-dd and soil pH. The highest Ca-dd was on the row of the plant with Intercropping system on slope 16-25% treatment amount 8,82 m.e/100 g soil and it had a correlation also to the highest pH i.e 5,43. If the intercropping system still used chicken manure as a fertilizer, it will be caused by the tea plant was calcium poisoning.